Study on Information Security Industry Efficiency Measurement Based on DEA-GRA - Wu, Songye; Zheng, Huixin; Lv, Caihong; Jiang, Jialing; Li, Shenghong (Transactions on Economics, Business and Management Research, 2024)
The operational efficiency of information security enterprises is of great significance to China's information security and even economic security. This paper constructs a DEA-GRA model to calculate the BCC efficiency decomposition of 30 listed companies and gives the amount of input redundancy and output insufficiency of non-DEA effective enterprises. This study also explores the grey correlation between the efficiency of super-efficient technologies and the environmental factors of where firms produce and sell. The results of the study show that the vast majority of non-DEA effective decision-making units in 2022 are in a state of decreasing size. The grey correlation analysis shows that the industrial cluster effect and scientific and technological investment in the production place, and the degree of development of the information security industry in the operation place have an important impact on the technical efficiency of information security enterprises.